An analysis of English language used in daily communication by students of Dayah or Islamic boarding schools - Ulya Zuhairati; Asnawi Muslem; Dohra Fitrisia (Universitas Syiah Kuala, 2022)
The objectives of this study were to analyze the policy regarding the language used and to know students’ perceptions about the use of English language for daily communication. This study used a mixed method and the researcher combined questionnaire, document analysis, and interview to gain the data needed. The subject of this study were 20 students of the sixth grade, and the leader of Dayah or Islamic boarding school. The research finding showed that the Dayah Modern Darul 'Ulum arranged the regulations regarding English language implementation and developed some programs to increase and motivate students to use the English language. In addition, from the questionnaire, in terms of the students’ perceptions, the finding of this research showed that 72,5% students perceive using English as daily language plays a good role in their speaking skill development, 93,3% students expected daily language program that can help them improve their English speaking skill, and 70% students perceive English language speaking implementation was good enough.